Quantifiable predictive features define epitope-specific T cell receptor repertoires - Dash, Pradyot; Fiore-Gartland, Andrew J.; Hertz, Tomer; Wang, George C.; Sharma, Shalini; Souquette, Aisha; Crawford, Jeremy Chase; Clemens, E. Bridie; Nguyen, Thi H. O.; Kedzierska, Katherine; La Gruta, Nicole L.; Bradley, Philip; et al. (Nature (London), 2017)
The authors characterize epitope-specific T cell repertoires, identify shared and recognizable features of TCRs, and develop tools to classify antigen specificity on the basis of sequence analysis. Defining T cell receptor repertoires In this study, Paul Thomas and colleagues use molecular genetic tools to analyse the diversity of epitope-specific T cell repertoires to characterize features that enable the prediction of T cell epitope specificity immunity based on sequence analysis. This manuscript is of broad interest to various fields ranging from basic immunology to applied immunotherapeutics and translational medicine. Elsewhere in this issue, Mark Davis and colleagues address the question of how T cell receptor sequences relate to antigen specificity and create an algorithm that predicts the human leukocyte antigen (HLA) restriction of the T cell receptor targets and helps to identify specific peptide major histocompatibility complex ligands. T cells are defined by a heterodimeric surface receptor, the T cell receptor (TCR), that mediates recognition of pathogen-associated epitopes through interactions with peptide and major histocompatibility complexes (pMHCs). TCRs are generated by genomic rearrangement of the germline TCR locus, a process termed V(D)J recombination, that has the potential to generate marked diversity of TCRs (estimated to range from 10 15 (ref. 1 ) to as high as 10 61 (ref. 2 ) possible receptors). Despite this potential diversity, TCRs from T cells that recognize the same pMHC epitope often share conserved sequence features, suggesting that it may be possible to predictively model epitope specificity. Here we report the in-depth characterization of ten epitope-specific TCR repertoires of CD8 + T cells from mice and humans, representing over 4,600 in-frame single-cell-derived TCRαβ sequence pairs from 110 subjects. We developed analytical tools to characterize these epitope-specific repertoires: a distance measure on the space of TCRs that permits clustering and visualization, a robust repertoire diversity metric that accommodates the low number of paired public receptors observed when compared to single-chain analyses, and a distance-based classifier that can assign previously unobserved TCRs to characterized repertoires with robust sensitivity and specificity. Our analyses demonstrate that each epitope-specific repertoire contains a clustered group of receptors that share core sequence similarities, together with a dispersed set of diverse ‘outlier’ sequences. By identifying shared motifs in core sequences, we were able to highlight key conserved residues driving essential elements of TCR recognition. These analyses provide insights into the generalizable, underlying features of epitope-specific repertoires and adaptive immune recognition.